STRATEGI PEMASARAN NOVI ULVIA MUA DALAM MENINGKATKAN OMSET PENJUALAN - Rahayu, Helena Putri; Habib, Muhammad Alhada Fuadilah (ITB AAS Indonesia Surakarta, 2024)
The development of business existence both in the field of goods and services, encourages new businesses to emerge. One of the growing businesses is the MUA service business. The mushrooming of MUA businesses in Indonesia has created quite tight market competition between business actors operating in the same field. So a special strategy is needed to win market competition. This study aims to determine Novi Ulvia MUA's marketing strategy in increasing sales turnover. This study uses descriptive qualitative research methods, using data collection techniques in the form of interviews, observation and documentation. The results of this study indicate that Novi Ulvia MUA was able to increase sales turnover and stabilize income with the 7P marketing mix strategy in the form of having a variety of make-up looks, the cosmetic products used are safe and have BPOM, using good quality cosmetic brands , provide affordable prices, have a variety of prices, provide cashback and discounts, easy to reach locations, have a large parking area, comfortable and clean gallery, carry out promotions through social media, word of mouth and wedding expo, owner has MUA BNSP certification , employees have superior quality human resources, conduct makeup training for employees, carry out a detailed process from preparing makeup tools to maintaining the quality of makeup until the event is over, have a photo album of previous makeup results with good quality makeup as a consumer reference, pay attention to the preparation dresses in the gallery so that they are always neat. The Marketing Mix strategy has proven to be able to increase Novi Ulvia MUA's sales.